ESG reporting and systemic risk: Evidence from European markets - Iulia Lupu; Gheorghe Hurduzeu; Gabriela Ţigu; Georgiana Coşoveanu; Radu Ion Filip (Amfiteatru Economic, 2025)
This study examined the relationship between Environmental, Social, and Governance (ESG) reporting quality and systemic financial risk in European equity markets. A novel index was developed to evaluate reporting quality, combining three dimensions: the scope of disclosures, the extent of exposure to reputational controversies, and the degree of alignment between sustainability scores and reputational risk indicators. Using daily return data for 600 companies listed in the STOXX Europe 600 index between 2010 and 2023, systemic risk was assessed through conditional value-at-risk differentials, capturing each firm's contribution to broader financial system vulnerabilities. The analysis adopted a comparative approach by grouping firms annually into high and low ESG reporting quality categories and comparing their average conditional value-at-risk contributions. Statistical tests consistently revealed that firms in the top index quartile exhibit significantly lower systemic risk contributions than those in the bottom quartile, particularly during market stress, such as the COVID-19 crisis and the Ukraine invasion. Quantile regression results further suggested that this mitigating effect was strongest in the upper tail of the risk distribution. The findings underscored the importance of credible reporting in improving financial stability and supporting regulatory initiatives that standardise disclosures across European capital markets, such as the Corporate Sustainability Reporting Directive and Sustainable Finance Disclosure Regulation frameworks.
Keywords: G15; G32; M14; Q56; 330; ESG reporting; ESG transparency; systemic risk; financial stability; controversies